Q. 224.3( 8 Votes )

In an isosceles Δ

Answer :


Given: AB = AC and BD AC


To Prove: BD2 – CD2 = 2CD × AD


In ∆BDC, using Pythagoras theorem we have,


(Perpendicular)2 + (Base)2 = (Hypotenuse)2


(BD)2 + (CD)2 = (BC)2 …(i)


In ∆BDA, using Pythagoras theorem we have,


(Perpendicular)2 + (Base)2 = (Hypotenuse)2


(BD)2 + (AD)2 = (AB)2


(BD)2 + (AD)2 = (AC)2 [ AB = AC]


Multiply this eq. by 2, we get


2(BD)2 + 2(AD)2 = 2(AC)2 …(ii)


Subtracting Eq. (ii) from (i), we get


CD2 – BD2 = BC2 – 2 AC2 + 2 AD2


= BC2 – 2 (AD +CD)2 + 2 AD2


= BC2 – 2 CD2 – 4 AD × CD


= BD2 + CD2 – 2 CD2 – 4 AD × CD


= BD2 – CD2 – 4 AD × CD


CD2 – BD2 –BD2 +CD2 = –4AD × CD


–2(BD2 – CD2) = –4AD × CD


BD2 – CD2 = 2CD × AD


Hence Proved


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Quiz- Test what you Know Part 2Quiz- Test what you Know Part 2Quiz- Test what you Know Part 245 mins
Quiz- Test what you KnowQuiz- Test what you KnowQuiz- Test what you Know45 mins
BPT ke Master Kaise Bane?BPT ke Master Kaise Bane?BPT ke Master Kaise Bane?46 mins
Pythagoras Theorem ki ApplicationPythagoras Theorem ki ApplicationPythagoras Theorem ki Application46 mins
Similarity - Apply it like a ChampSimilarity - Apply it like a ChampSimilarity - Apply it like a Champ45 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

In Fig. 3,<Mathematics - Board Papers